2014
DOI: 10.2174/13816128113199990540
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation and Activation of Syncytin-1 Gene in Endometriotic Tissue

Abstract: Syncytin-1 plays a critical role in the maintenance of normal pregnancy by mediating the formation of syncytiotrophoblasts through a fosugenic action. Encoded by the human endogenous retrovirus envelope gene HERV-W, syncytin-1 trophoblast-specific expression is controlled by epigenetic mechanisms. In non-placental tissues, the syncytin-1 gene is suppressed by hypermethylation in the LTR promoter region. Hypomethylated and activated syncytin-1 gene is found in placental trophoblast lineages and malignant cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Finally, two studies reported a high HERV-W expression in endometriotic tissues, even though no great differences were found with respect to control tissues [ 14 , 57 ]. This Syncytin-1 upregulation, dependent on the hypomethylation of its promoter, has been proposed to be involved in endometriotic lesion development [ 73 ].…”
Section: Syncytin-1 Expression In Placental Pathologiesmentioning
confidence: 99%
“…Finally, two studies reported a high HERV-W expression in endometriotic tissues, even though no great differences were found with respect to control tissues [ 14 , 57 ]. This Syncytin-1 upregulation, dependent on the hypomethylation of its promoter, has been proposed to be involved in endometriotic lesion development [ 73 ].…”
Section: Syncytin-1 Expression In Placental Pathologiesmentioning
confidence: 99%
“…61 Passive demethylation, occurring due to loss of maintenance methylation activity conferred by DNMTs, may also contribute to relieving gene repression. 62, 63 The potential involvement of passive demethylation in regulating KCNMB1 expression in pregnancy could not be excluded and merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The altered phenotype of endometriotic cells has a strong epigenetic component, and variation in DNMT is a putative mechanism affecting DNA methylation in diseased cells (2932, 5052). Here we demonstrated that EIUM and E-OSIS express all three DNMT isoforms, but that IVD treatment reduced DNMT3B only in healthy stromal cells.…”
Section: Discussionmentioning
confidence: 99%